Primary Ewing Sarcoma of the Thyroid—Eight Cases in a Decade: A Case Report and Literature Review - Kabata, Paweł; Kaniuka-Jakubowska, Sonia; Kabata, Wanda; Lakomy, Joanna; Biernat, Wojciech; Sworczak, Krzysztof; Jaśkiewicz, Janusz; Świerblewski, Maciej (Frontiers in Endocrinology, 2017)
Sarcomas represent less than 1% of all malignant tumors found in the thyroid. Of these, primary extraosseous sarcoma has been reported only a few times in the past decade. We present the case of a 34-year old male who had a fast-growing hard mass in the lower left neck. FNA was inconclusive. Core needle biopsy revealed the diagnosis of an Ewing sarcoma/primitive neuroectodermal tumor. Mutation of EWSR1 was confirmed using the FISH method. Following treatment by neoadjuvant chemotherapy we observed clinical, radiological, and finally histopathological remission. This was followed by a left-sided isthmolobectomy with unilateral cervical lymph node dissection by lateral lymphadenectomy, which revealed no residual disease. Post-treatment radiotherapy was administered but discontinued upon the patient’s request. After 18 months of observation, the patient had no recurrence or metastasis and required L-thyroxine supplementation. We discuss our case using a comparative literature review to the few other known case reports.